THE DEVELOPMENT OF PhET-ASSISTED INQUIRY-BASED ELECTRONIC WORKSHEETS TO IMPROVE COMMUNICATION AND COLLABORATION SKILLS - Tanti Rahayu; Widodo Setiyo Wibowo (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2023)
Communication and collaboration skills are part of the 21st century skills that are very important for students to possess. Science learning with certain characteristics can be a means to develop these abilities. The aims of this study were: 1) to develop a viable PhET-assisted inquiry-based electronic worksheets, (2) to find out the practicality of the developed products based on student responses, (3) to test the effect of using the product to increase communication skills, and (4) to test the effect of using the product to increase collaboration skills. This research was a Research and Development (R&D) with a 4-D model consisted of define, design, develop, and disseminate. Product trial design using one group pretest-posttest on 32 students of class VIII B at SMPN 05 Depok. The data collection instruments consisted of product validation sheets, student response questionnaires, communication skills observation sheets and collaboration skills observation sheets. The product viability data were examined qualitatively and quantitatively descriptively. The paired sample t-test and effect size analysis were used to check the effect of the product toward communication and collaboration skills. The results show that PhET-assisted inquiry-based electronic worksheets are: 1) declared suitable for use in science learning, (2) considered practical for use in science learning, (3) effective in improving communication skills, (4) effective in improving collaboration skills.